Centering context when characterizing food environments: The potential of participatory mapping to inform food environment research - Downs, Shauna; Manohar, Swetha; Staromiejska, Wiktoria; Keo, Chanvuthy; Say, Sophea; Chhinh, Nyda; Fanzo, Jessica; Sok, Serey (Frontiers Media, 2024)
Food environments are a critical place within the food system to implement interventions aimed at enabling sustainable diets. In this perspective article, we argue for the need for food environment research to more comprehensively examine the different types of food environments that people access within their communities to ensure that interventions and programs are better aligned with people’s lived experiences. We highlight the potential ways in which participatory mapping (PM) can be leveraged to better design food environment research by: (1) identifying the different food environment types that are accessed within a given community; (2) providing insight into the timing for data collection; (3) informing the prioritization of where to conduct food environment assessments; and (4) highlighting the dynamism of food environments over time (e.g., across a given day or across seasons). We provide a case study example of the application of PM and the lessons learned from it in Cambodia. By conceptualizing food environments in a more comprehensive way, from the perspective of the people living within a given community, we will be able to measure food environments in a way that more closely aligns with people’s lived experiences.